A study of the software tools capabilities in translating UML models to PN models - Rajabi, Bassam Atieh; Malaysia, Kuala Lumpur; Lee, Sai Peck (2009)
Integrating Object Oriented (OO) modeling language and Petri Net (PN) modeling is important to gather complementary benefits of these two modeling languages. OO technology is used to describe the static aspects of systems because of its powerful structuring capabilities, whereas PN is used to model the behavioral aspects for concurrent and non deterministic applications. PN is an executable modeling language; the behavior of the model can be validated and verified automatically using formal specifications and mathematical foundation. In this research, a comparative study for the representation capabilities of the software tools in translating OO models to PN models will be provided and discussed.